Analysis of Tourism Village Attraction Development Strategy as a Sustainable Tourism Destination: Case Study of Lahang Village in Sukabumi Regency - Jason, Andrew; Srihadi, Cecilia; Riwoe, Febry Lodwyk Rihe (Jurnal Ilmiah Pariwisata Kesatuan, 2024)
The goal of tourism development is to promote equity of opportunity for tourism actors so that they can attempt to benefit and be able to deal with the dynamic transformation of the tourism sector into a priority sector in encouraging community economic growth, increasing regional foreign exchange, empowering the community's economy, expanding employment and business opportunities, and introducing product marketing to realize community welfare and create sustainable tourism destinations. This research is carried out in Lahang Village, Sukabumi Regency, and employs a descriptive research with a qualitative methodology. Multiple interviews with pertinent informants served as the primary data source, while secondary data came from reading materials connected to the research issue. ways for gathering research data through observation and interviews. While the research instrument is researcher himself and auxiliary resources like interview guidance and other tools serve as the research instrument. Based on the research's findings, it was revealed that the local community first rejected Lahang Village, but that via discussion and socialization, the Management, Pokdarwis, and Village Government were able to settle the licensing concerns. In addition to increasing hospitality, improving and maintaining facilities and infrastructure, and enlisting the local community as a labor force for tourism management, Lahang Village Management has pursued and carried out a number of developments. The understanding and passion of some residents who want to see their village transformed is a supporting aspect. Keywords: Development, Tourism Village, Sustainable Tourism